Identification of bioactive compounds in extract fraction red seaweed (Eucheuma cottonii) - Agusman, Indra; Diharmi, Andarini; Sari, N Ira (Universitas Malikussaleh, 2022)
Seaweed is a biological resource that is rich in nutrients and bioactive compounds. This study aims to determine qualitatively and quantitatively the bioactive compounds (flavonoids, alkaloids, steroids/terpenoids, saponins and phenols) from extracts and fractions of Eucheuma cottonii. The method used is an experiment by conducting a series of experiments by extracting and fractionating E. cottonii and the data were analyzed descriptively. The treatments used were organic solvents with different polarity levels (methanol, n-hexane, ethyl acetate, and butanol) for extraction and fractionation. Parameter analysis consisted of qualitative phytochemical tests (flavonoids, alkaloids, steroids/terpenoids, saponins and phenols) and quantitatively determined the total content of alkaloids, flavonoids, and saponins. The results of the phytochemical test of methanol extract qualitatively produced alkaloids, flavonoids, steroids/terpenoids, and saponins. The n-hexane fraction contains steroids/terpenoids and saponins. The ethyl acetate fraction contains alkaloids, flavonoids and steroids/terpenoids and the butanol fraction contains alkaloids. The results of quantitative analysis of the n-hexane extract fraction showed that the content of saponins was 0.23%, alkaloids and flavonoids were 0.16% and 0.09% in the ethyl acetate fraction, while the alkaloid content was 0.09% in the butanol fraction.Keywords: fractionation; organic solvent; phytocemical; quantitative